Dissolution of cellulose in dimethyl phosphate ionic liquid solutions. (27th May 2019) - Thomas, Marie F.; Chen, Anne; Yuan, Mike; Agababayev, Adam; Harris, Chaudhary
Abstract: Ionic liquids are organic salts that have melting points below 100 °C and they may serve as environmentally friendlier alternatives to the toxic and/or corrosive chemicals usually used to process biomass. However, ionic liquids can be viscous and expensive. A series of dimethyl phosphate ionic liquids with varying alkyl chain lengths have been synthesized and combined with solvents such as dimethyl sulfoxide and dimethylformamide. The resulting solutions have been used to dissolve cellulose. In general, it would appear that the length of the alkyl chain (up to a carbon chain length of six) does have some effect on the dissolution of cellulose. GRAPHICAL ABSTRACT: UF0001